Investigation of the effect of human intestinal microbiota bacteria on the bioremediation of commonly used pesticides by liquid chromatography - Ahmet Aktaş; İlker Aras Göçer; Yaşar Naki̇poğlu (The Microbe)
Pesticides are defined as chemical substances used to protect a variety of plants from parasite infestation. Due to their chemical structure, they have a long half-life and the capacity to form residues, and therefore many fruits can contain pesticide residues. Pesticide exposure may occur via inhalation, ingestion, or direct contact. The European Commission's directive restricts the use of pesticides and sets a residue limit of 0.1 μg/L. The aim of this study is to determine the impact of bacteria in the human gut microbiota on the biodegradation of commonly used pesticides. This study investigated the effects of five bacterial strains, namely Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae (K. pneumoniae), and Enterococcus faecalis (E. faecalis), isolated from neonatal rectal swab samples and, blood samples on the degradation of pesticides using liquid chromatography and mass spectrometry. (LC-MS). All bacteria resulted in significant pesticide degradation (p < 0.05). E. faecalis caused significantly more degradation than K. pneumoniae (p = 0.043). No significant difference was observed between the degradation rates of pesticides and other bacteria (p > 0.05). The results demonstrate that bacteria can be used to clean water and soil contaminated with pesticides. Therefore, we do not have information about possible mutations in DNA. This is the biggest limitation of this study. Therefore, our study data needs to be supported with study data including more strains and examining bacterial DNA with new generation sequencing methods.